FAMILY DIADOCIDIIDAE - Falaschi, Rafaela Lopes (Zootaxa, 2016)
Diadocidiidae are a small family belonging to the suborder Bibionomorpha. Three species were described for the Neotropical region, two from Costa Rica and one from Brazil, and one additional undescribed species from Colombia is reported here for the first time.